Piezoelectric energy harvesting from machine vibrations for wireless sensor system - Panthongsy, Phosy; Isarakorn, Don; Sudhawiyangkul, Thapanun; Nundrakwang, Songmoung (My University, 2015)
In recent years, wireless sensor network is used in a variety of applications and highly required. These wireless sensor network is powered by the battery with limit energy. Therefore, the integration of energy harvester and wireless sensor network has received more attention because it can prolong the lifetime of battery in a sensor node. The focus of this paper is to design the energy harvesting device from machine vibrations for wireless sensor node, which the amplitude and frequency of vibration source were contributed on the design. The structure of energy harvesting devices is a resonant type piezoelectric energy harvester with a proof mass at the tip of the beam for tuning its resonant frequency. The proposed piezoelectric energy harvesters were then designed and analyzed by using Finite Element Method (FEM) to optimize the natural frequency of the harvester. Then, the prototype energy harvesters were made and mounted to a vibration source for experiments. The result reveals that the optimal piezoelectric energy harvester can generate the output power of 82.29 μW at the resonant frequency of 50 Hz.
Keywords: Energy harvesting; Machine vibrations; Piezoelectric transduction